Predicting the Clinical Outcome of Allogeneic Hematopoietic Stem Cell Transplantation: The Long and Winding Road toward Validated Immune Biomarkers - Forcina, Alessandra; Noviello, Maddalena; Carbone, Maria R.; Bonini, Chiara; Bondanza, Attilio (Frontiers in Immunology, 2013)
The clinical outcome of allogeneic hematopoietic stem cell transplantation (HSCT) is strongly influenced from the potential complications arising during the delicate phase of post-transplant immune restoration. The quantitative aspects of immune-cell repopulation after HSCT and the qualitative features their functional restitution have been extensively reported. Nevertheless, measurable immune biomarkers predicting the clinical outcome of HSCT await formal validation. The aim of this review is an appraisal of most studies published so far on the predictive value of different T and NK-cell biomarkers after HSCT with emphasis on defined thresholds endorsed by multivariate analysis.